Transparent protective sheet for solar cell modules

A transparent protective sheet composed of PET and ETFE layers addresses the issue of acetic acid gas diffusion in solar cell modules by maintaining high water vapor barrier properties and promoting gas release, effectively protecting the solar cell elements.

JP7663137B2Active Publication Date: 2025-04-16DAI NIPPON PRINTING CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2024016850
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-02-07
Publication Date
2025-04-16
Estimated Expiration
2038-10-30

AI Technical Summary

Technical Problem

Solar cell modules face challenges with the decomposition of ethylene-vinyl acetate copolymer (EVA) encapsulating materials in high temperature and humid environments, leading to the generation of acetic acid gas, which can negatively affect the solar cell elements, and existing transparent protective sheets with high water vapor barrier properties fail to completely prevent the diffusion of this gas.

Method used

A transparent protective sheet made of polyethylene terephthalate (PET) with a base resin layer and a weather-resistant ETFE layer, which maintains high water vapor barrier properties while promoting the release of acetic acid gas generated inside the solar cell module.

Benefits of technology

The proposed solution effectively prevents water vapor intrusion into the solar cell module while facilitating the release of acetic acid gas, thereby protecting the solar cell elements and maintaining the module's efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663137000002
    Figure 0007663137000002
  • Figure 0007663137000003
    Figure 0007663137000003
  • Figure 0007663137000001
    Figure 0007663137000001
Patent Text Reader

Abstract

To provide a transparent protective sheet which can promote release of harmful acetic gas generated inside a solar cell module to outside the module while holding such high water vapor barrier property as to prevent intrusion of water vapor from the outside the solar cell module.SOLUTION: A transparent protective sheet 1 has such a multilayer structure that a base material resin layer 11 occupying 75% or more of total thickness by a thickness ratio, and a weather-resistant resin layer 13 are stacked, and a vapor-deposited layer composed of an inorganic compound and a thin film layer composed of an inorganic compound are not included, wherein total thickness exceeds 300 μm, the base material resin layer 11 is polyethylene terephthalate, the weather-resistant resin layer 13 is a copolymer of tetrafluoroethylene and ethylene, and water vapor permeability (pw) measured at a test temperature of 40°C according to JIS K 7126-1 as the whole resin sheet of the multilayer structure is 0.8 cm3 / (m2 24h atm) or less.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent protective sheet for a solar cell module. [Background technology]

[0002] In recent years, solar cells have been attracting attention as a clean energy source due to the growing awareness of environmental issues. In general, a solar cell module constituting a solar cell is configured by laminating a transparent front substrate, a front-side sealing material, a solar cell element, a back-side sealing material, and a transparent protective sheet in this order from the light-receiving surface side, and has a function of generating electricity when sunlight is incident on the solar cell element. Note that a transparent glass substrate is often used as the transparent front substrate, but a protective sheet similar to that on the back side can also be used.

[0003] Since solar cell modules are used outdoors for a long period of time, each of the above-mentioned components constituting the solar cell module is required to have durability capable of withstanding the harsh outdoor environment for a long period of time. In particular, high weather resistance is required for the protective sheet placed on the outermost surface of the solar cell module. As such, fluorine-based films have been widely used as protective sheets for solar cell modules that require high weather resistance. However, in response to the demand for reducing manufacturing costs and weight, a protective sheet has been proposed in which an economically advantageous polyester resin sheet such as polyethylene terephthalate (PET) is used as a base resin layer that occupies the main part of the protective sheet (see Patent Document 1).

[0004] On the other hand, in solar cell modules, as an encapsulant arranged mainly for the purpose of protecting solar cell elements from external impact, an encapsulant based on ethylene-vinyl acetate copolymer (hereinafter also referred to as "EVA") is generally used from the viewpoints of processability, workability, manufacturing cost, etc. However, EVA tends to gradually decompose during long-term use in a hot and humid environment, and this decomposition is further accelerated by high-temperature water vapor. In solar cell modules equipped with an encapsulant based on EVA, it has been considered problematic that acetic acid gas generated by the decomposition adversely affects solar cell elements.

[0005] In response to this, a protective sheet has been developed that prevents the intrusion of moisture, which is a cause of the generation of acetic acid gas, by arranging a resin sheet on which a metal vapor deposition film such as aluminum oxide is formed as a barrier layer to extremely reduce water vapor permeability (see Patent Document 2). For example, it is possible to reduce the generation of acetic acid gas to a certain degree by using a protective sheet with a barrier layer in which a transparent alumina vapor deposition film is vapor-deposited on a polyethylene terephthalate resin substrate.

[0006] However, even when a solar cell module is constructed by combining a transparent protective sheet having a very high water vapor barrier property with a general-purpose encapsulant having EVA as a base resin as disclosed in Patent Document 2, it is not possible to completely prevent the generation of acetic acid gas over a long period of time. It has been recognized that when acetic acid gas originating from the encapsulant is generated inside a solar cell module, the high barrier property of the transparent protective sheet blocks the gas from diffusing toward the outside of the module, and most of the gas diffuses to the periphery of the solar cell element, which warps and adversely affects the solar cell element. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Special Publication No. 2010-519742 [Patent Document 2] JP 2012-199379 A Summary of the Invention [Problem to be solved by the invention]

[0008] In view of the above circumstances, the object of the present invention is to provide a transparent protective sheet that uses economical polyethylene terephthalate as a base resin, and that maintains high water vapor barrier properties to prevent the intrusion of water vapor from outside the solar cell module, while at the same time promoting the release of harmful gases (acetic acid gas) generated inside the solar cell module to the outside of the module. [Means for solving the problem]

[0009] The present inventors have found that the above-mentioned problems can be solved by using an economical polyethylene terephthalate (PET) as a resin for forming the base resin layer that occupies the main part of the transparent resin sheet, and using a relatively expensive copolymer of tetrafluoroethylene and ethylene (ETFE), which has a higher gas permeability than PET, as an auxiliary resin for forming a weather-resistant resin layer that protects the base resin layer, and have completed the present invention. Specifically, the present invention provides the following.

[0010] (1) A transparent resin sheet having a light transmittance of 70% or more in the wavelength region of 400 nm or more and 1,200 nm or less, which is formed by laminating a base resin layer that occupies 75% or more of the total thickness in terms of thickness ratio and a weather-resistant resin layer, the base resin layer being polyethylene terephthalate, the weather-resistant resin layer being a copolymer of tetrafluoroethylene and ethylene, and being configured without including any deposition layer or thin film layer made of an inorganic compound, and the water vapor transmission rate (pw) of the entire layer measured at a test temperature of 40°C according to JIS K 7126-1 is 1.2 cm 3 / (m 21.4。 Transparent protective sheet for solar cell module, wherein the ratio (pa / pw) of the acetic acid permeability (pa) measured at a test temperature of 40°C according to JIS K 7126-1 in all layers to the water vapor permeability (pw) is 1.4 or more.

[0011] (2) The water vapor permeability (pw) is 0.8 cm 3 / (m 2 24h·atm) or less.

[0012] (3) A solar cell module comprising a solar cell element, a front-side sealing material and a back-side sealing material laminated on both sides of the solar cell element, and a protective sheet laminated on the surface of either the front-side sealing material or the back-side sealing material, wherein the solar cell element is a double-sided light-receiving solar cell element, the front-side sealing material and the back-side sealing material have ethylene-vinyl acetate copolymer (EVA) as a base resin and have a light transmittance of 70% or more, and the protective sheet is the transparent protective sheet described in (1) or (2) and is disposed on the outermost surface of either the solar cell module. Effect of the Invention

[0013] According to the present invention, it is possible to provide a transparent protective sheet that uses economical polyethylene terephthalate as a base resin, and that maintains high water vapor barrier properties to prevent the intrusion of water vapor from outside a solar cell module, while at the same time promoting the release of harmful gases (acetic acid gas) generated inside the module to the outside of the module. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a cross-sectional view showing an example of the layer structure of a solar cell module using the transparent protective sheet for a solar cell module of the present invention. [Diagram 2] FIG. 1 is a cross-sectional view illustrating a schematic layer structure of a transparent protective sheet for a solar cell module of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The transparent protective sheet for a solar cell module of the present invention will be described below. Note that the present invention is not limited to the embodiments described below.

[0016] <Solar cell module> First, the overall structure of a solar cell module 10 using the transparent protective sheet 1 for a solar cell module of the present invention will be described. The solar cell module 10 is configured by sequentially stacking a transparent front substrate 4, a front-side sealing material 3, a solar cell element 5, a back-side sealing material 2, and a transparent protective sheet 1, as shown in FIG. 1. The resin layer in which the front-side sealing material 3 and the back-side sealing material 2 are combined and integrated is also simply referred to as a sealing material. The use of the transparent protective sheet 1 of the present invention is not necessarily limited to being disposed on the back side of a solar cell module as described above, and it can also be disposed on the front side of the solar cell module 10 as a transparent front substrate.

[0017] Here, it is assumed that the solar cell module 10 of the present invention is a see-through type or a double-sided light-collecting type solar cell module. Therefore, the transparent protective sheet 1 is naturally required to have a high degree of transparency. Here, in this specification, "transparent" means that "light rays in the visible light region and the near-infrared region can be transmitted", and more specifically, it means that "the light transmittance at a wavelength of 400 nm or more and 1200 nm or less is 70% or more, preferably 80% or more, in the entire wavelength region." Furthermore, in this specification, "light transmittance" refers to the light transmittance measured in accordance with JIS-K-7105 or JIS-K-7136, unless otherwise specified.

[0018] 2, the transparent protective sheet 1 has a weather-resistant resin layer 13 formed on one surface and an easy-adhesion layer 14 formed on the other surface. In the solar cell module 10, the transparent protective sheet 1 is disposed with the easy-adhesion layer 14 facing the bonding surface side with the back-side sealing material 2.

[0019] The back-side sealing material 2 and the front-side sealing material 3 can be appropriately selected from various resins that have been conventionally used as sealing materials for solar cell modules. However, as a combination of the transparent protective sheet 1 and the sealing material, it is preferable to use a transparent sealing material whose base resin is ethylene-vinyl acetate copolymer (EVA) resin.

[0020] As described above, the transparent protective sheet 1 of the present invention can provide the function and effect of promoting the release of acetic acid gas generated in a solar cell module. In the above-mentioned see-through type or double-sided light-receiving type solar cell module, light hits the encapsulant from both sides of the module, so decomposition of EVA resin and generation of acetic acid gas are more likely to be promoted than in a typical single-sided light-receiving type module. For the above reasons, the above-mentioned function and effect provided by the transparent protective sheet 1 is particularly necessary in a solar cell module constructed using a transparent encapsulant whose base resin is EVA resin.

[0021] A transparent glass substrate is usually used as the transparent front substrate 4. However, various transparent resin sheets having weather resistance, including the transparent protective sheet of the present invention, can also be used as the transparent front substrate 4.

[0022] [Solar cell module manufacturing method] The solar cell module 10 can be manufactured by integrating the above-mentioned components by, for example, vacuum thermal lamination. The lamination temperature is preferably in the range of 110°C to 190°C, more preferably 130°C or higher. The lamination time is preferably in the range of 5 minutes to 60 minutes. This lamination is performed in a manner in which the easy-adhesion layer 14 of the transparent protective sheet 1 and the back-side sealing material 2 are placed face-to-face and then heated and pressed together. This allows the high adhesiveness of the easy-adhesion layer 14 at the interface between the transparent protective sheet 1 and the back-side sealing material 2 to be fully expressed.

[0023] <Transparent protective sheet> As shown in FIG. 2, the transparent protective sheet 1 is a multi-layered resin sheet including a base resin layer 11 and a weather-resistant resin layer 13. The base resin layer 11 is a resin layer that occupies a major portion of the transparent protective sheet, specifically, a portion that occupies 75% or more of the total thickness of the sheet. The weather-resistant resin layer 13 is a resin layer that occupies 25% or less of the total thickness. The base resin layer 11 and the weather-resistant resin layer 13 are preferably laminated via an adhesive layer 12. In addition, it is preferable that an easy-adhesion layer 14 is formed on the surface of the base resin layer 11 on the side on which the weather-resistant resin layer 13 is not laminated, in order to enhance adhesion with the back-side sealing material 2.

[0024] Moreover, the transparent protective sheet 1 is configured without including any of a vapor deposition layer and a thin film layer made of an inorganic compound. The "vapor deposition layer made of an inorganic compound" is, for example, a transparent alumina vapor deposition layer as disclosed in Patent Document 2. The "thin film layer made of an inorganic compound" refers to, for example, a metal foil layer such as an aluminum foil when the aluminum foil is arranged as a barrier layer. The arrangement of these inorganic compound-based barrier layers effectively contributes to extremely reducing the water vapor permeability of the protective sheet, but is inferior to the transparent protective sheet 1 of the present invention in terms of inhibiting the release of acetic acid gas. Furthermore, a general metal foil layer is not suitable for use in the solar cell module 10 according to the present invention in that it cannot maintain the transparency of the entire solar cell module. The arrangement of these inorganic compound-based barrier layers is also not preferable in that the material cost increases compared to the case where the transparent protective sheet 1 of the present invention is arranged as a barrier layer.

[0025] The transparent protective sheet 1 having the above-mentioned structure has a water vapor transmission rate (pw) of 1.2 cm or less, measured at a test temperature of 40° C. according to JIS K 7126-1 in all layers. 3 / (m 2The types of resin materials of the base resin layer 11 and the weather-resistant resin layer 13 and the thickness ratio of both layers are optimized so that the ratio (pa / pw) of the acetic acid permeability (pa) measured under the same conditions to the water vapor permeability (pw) measured in all layers at a test temperature of 40°C in accordance with JIS K 7126-1 is 1.4 or more.

[0026] For example, if the transparent protective sheet is to have a thickness of about 150 μm, and the transparent protective sheet is made of a single-layer resin sheet made of PET resin, the water vapor permeability (pw) can be made sufficiently small; however, in this case, it is difficult to simultaneously obtain a sufficiently large acetic acid permeability (pa).

[0027] Therefore, the resin material of the substrate resin layer 11, which occupies the main part of the transparent protective sheet 1 (part having a thickness ratio of 75% or more), is left as PET resin, which has excellent cost performance, and the weather-resistant resin layer 13, which is laminated additionally, is formed from ETFE, which is more expensive than PET but has high gas permeability. This makes it possible to maintain the economic advantage of forming the substrate resin layer 11 from PET and to sufficiently improve the acetic acid permeability (pa) while maintaining the required water vapor permeability (pw).

[0028] Here, the acetic acid permeability (pa) (cm) measured at a test temperature of 40°C according to JIS K 7126-1 in all layers of the transparent sheet 3 / (m 2 ·24h·atm)) and water vapor permeability (pw) (cm 3 / (m 2In this specification, the "ratio (pa / pw)" of the above (p / a) and the relative humidity (p / a) (24h atm) is also referred to as the "acetic acid / water permeability ratio (pa / pw)". As will be shown later in the examples, if the transparent sheet is formed only from PET, the value of this "acetic acid / water permeability ratio (pa / pw)" will be less than 1.4 regardless of the total thickness. By auxiliary laminating a weather-resistant resin layer formed using ETFE within an appropriate relative thickness range, the value of this "acetic acid / water permeability ratio (pa / pw)" can be increased to 1.4 or more without changing the total thickness of the transparent protective sheet. And, according to the present invention, it is possible to provide a transparent protective sheet that can sufficiently promote the release of acetic acid gas while maintaining the water vapor barrier properties required for various transparent protective sheets of different thicknesses, not limited to the above protective sheet with a total thickness of about 150 μm.

[0029] The total thickness of the transparent protective sheet 1 can be appropriately selected within an appropriate thickness range depending on the level of water vapor barrier property required. For example, when the water vapor transmission rate (pw) of the transparent protective sheet 1 is 1.2 cm 3 / (m 2 If the range of acetic acid / water permeability (pa / pw) or less is acceptable, the total thickness of all layers of the transparent protective sheet 1 can be thinned to about 155 μm to 165 μm. In this case, a transparent protective sheet 1 with an acetic acid / water permeability ratio (pa / pw) of 1.4 or more due to the layer structure can reduce the acetic acid permeability (pa) to 1.7 cm 3 / (m 2 ·24h·atm) or more.

[0030] On the other hand, the water vapor permeability (pw) of the transparent protective sheet 1 is set to a maximum of 0.8 cm 3 / (m 2 If it is necessary to keep the water vapor transmission rate (pw) at a lower value of 0.8 cm or less, the total thickness of all layers of the transparent protective sheet 1 can be set to about 310 μm, and the water vapor transmission rate (pw) of the transparent protective sheet having the base resin layer 11 made of PET can be kept at 0.8 cm or less. 3 / (m 2In this case, for example, if the protective sheet is made of only PET film, the acetic acid permeability (pa) is 1.0 cm 3 / (m 2 24h atm), but with Transparent Protective Sheet 1, which has an acetic acid / water permeability ratio (pa / pw) of 1.4 or more due to the layer structure, the acetic acid permeability (pa) is reduced to 1.1 cm 3 / (m 2 ·24h·atm) or higher.

[0031] The transparency of the transparent protective sheet 1 is required to satisfy the requirement that the light transmittance in the wavelength range of 400 nm or more and 1200 nm or less is 70% or more, and preferably 80% or more, over the entire wavelength range. In producing the transparent protective sheet 1, materials for forming each layer, which will be described in detail below, are selected within a range that satisfies this requirement.

[0032] [Base resin layer] In the transparent protective sheet 1, the base resin layer 11 is formed using polyethylene terephthalate (PET) as a base resin. PET is a resin that is advantageous not only in terms of electrical insulation, heat resistance, chemical resistance, dimensional stability, and moldability, but also in terms of economy. Among various PET films, a hydrolysis-resistant transparent PET film (e.g., "Lumirror" (manufactured by Toray Industries, Inc.)) can be particularly preferably used.

[0033] The thickness of the base resin layer 11 is not limited to a specific thickness as long as it accounts for 75% or more of the total thickness of the transparent protective sheet 1, but is preferably 150 μm or more and 300 μm or less. For example, a resin film as thin as possible (a resin film with a thickness of about 150 μm) may be selected within a range that meets the required level of water vapor permeability, or a resin film with a larger thickness (a resin film with a thickness of about 300 μm) may be selected to increase the water vapor permeability. If the thickness of the base resin layer 11 is less than 150 μm, it is not preferable in terms of reduced insulation. Furthermore, if the thickness exceeds 300 μm, it is not preferable in terms of processability. The base resin layer 11 may be composed of a single-layer resin film of a predetermined thickness, but may also be composed of a multi-layer resin film of a predetermined thickness in which a plurality of resin films are laminated together.

[0034] The substrate resin layer 11 may contain components other than the above resins as long as they do not impede the effects of the present invention. For example, various plastic compounding agents, additives, other resins, etc. can be added for the purpose of improving or modifying processability, heat resistance, light resistance, weather resistance, mechanical properties, dimensional stability, antioxidant properties, slipperiness, mold releasability, flame retardancy, antifungal properties, electrical properties, etc. The amount of these additives, etc. added is not particularly limited, and can be added arbitrarily depending on the purpose. Examples of common additives include lubricants, crosslinking agents, antioxidants, light stabilizers, fillers, lubricants, reinforcing fibers, reinforcing agents, antistatic agents, flame retardants, flame retardants, foaming agents, antifungal agents, modifying resins, etc.

[0035] [Weather-resistant resin layer] In the transparent protective sheet 1, the weather-resistant resin layer 13 is formed using a copolymer of tetrafluoroethylene and ethylene (ETFE) as a base resin. Although expensive, ETFE is a fluorine-based resin that satisfies the requirements for transparency that the transparent protective sheet 1 should have, has excellent weather resistance, and is also excellent in hydrolysis resistance, among various resin materials that have been used for the outermost layer to ensure weather resistance in protective sheets for solar cell modules. Among various ETFE films, for example, "Aflex 25ND" (manufactured by Asahi Glass Co., Ltd.) can be preferably used.

[0036] The thickness of the weather-resistant resin layer 13 is not limited to a specific thickness, so long as it accounts for 25% or less of the total thickness of the transparent protective sheet 1, mainly from the viewpoint of economic efficiency. However, it is preferably 10 μm or more and 50 μm or less. If the thickness of the weather-resistant resin layer 13 is less than 10 μm, it is not preferable because the effect of improving the acetic acid permeability (pa) is difficult to achieve. The weather-resistant resin layer 13 may be composed of a single-layer resin film of a predetermined thickness, but it can also be composed of a multi-layer resin film of a predetermined thickness in which a plurality of resin films are laminated together.

[0037] As with the base resin layer 11, the weather-resistant resin layer 13 may contain various additives other than the resins exemplified above, as long as they do not impede the expression of the effects of the present invention.

[0038] [Adhesive layer] The adhesive layer 12 is a layer that has the function of adhering the weather-resistant resin layer 13 to the surface of the base resin layer 11. This layer is required to have the same transparency as the other layers that constitute the transparent protective sheet 1. As the adhesive that is the main material of the adhesive for forming the adhesive layer 12, any of various conventionally known transparent adhesives, such as urethane adhesives and acrylic adhesives, can be appropriately selected as long as it satisfies the requirement for transparency.

[0039] The thickness of adhesive layer 12 may be appropriately changed depending on the transparency and adhesive strength required for transparent protective sheet 1, and a preferred thickness range is from 1.0 μm to 10 μm.

[0040] For example, a two-liquid adhesive consisting of a base agent containing a mixture of polyurethane diol and aliphatic polycarbonate diol, and a curing agent can be used as the transparent adhesive that is the main material of the adhesive layer 12. In this case, the polyurethane diol and aliphatic polycarbonate diol that constitute the base agent are both polyols having hydroxyl groups, and an adhesive that reacts with a curing agent having an isocyanate group can be preferably used.

[0041] The polyurethane diol, which is the main component, is a polyurethane having a urethane structure as a repeating unit and having hydroxyl groups at both ends. The hydroxyl value of the polyurethane diol is preferably in the range of 10 mgKOH / g to 50 mgKOH / g. The polyurethane diol is obtained by reacting an aliphatic polycarbonate diol, 1,6-hexanediol, and isophorone diisocyanate as the main component of an adhesive to improve its adhesiveness and weather resistance.

[0042] The above-mentioned aliphatic polycarbonate diol may be a commercially available product. In order to obtain an adhesive having excellent durability, weather resistance, heat resistance, and hydrolysis resistance, for example, an aliphatic polycarbonate diol having a number average molecular weight of 1000 (manufactured by Asahi Kasei Chemicals Corporation, product name "Duranol T5651") or an aliphatic polycarbonate diol having a number average molecular weight of 2000 (manufactured by Asahi Kasei Chemicals Corporation, product name "Duranol T5662") may be suitably used.

[0043] In addition, the solvent that can be used when reacting an aliphatic polycarbonate diol, 1,6-hexanediol, and isophorone diisocyanate is not particularly limited as long as it can dissolve these compounds and does not react with the solvent. From the viewpoints of compatibility and processability during lamination, examples of the solvent that can be used include carboxylic acid ester-based solvents such as ethyl acetate.

[0044] In addition to transparency, it is preferable that the adhesive layer 12 of the transparent protective sheet 1 has ultraviolet blocking properties to protect the base resin layer 11 from ultraviolet rays. For this purpose, it is preferable to add a UV absorber in a predetermined range to the adhesive layer 12. Specifically, the adhesive layer 12 has a UV absorber content of 0.3 g / m per unit area. 2 The content of ultraviolet absorbing agent is required to be 1.3 g or less, and 0.5 g / m per unit area. 2 More than 1.0g / m 2 It is preferable that the following ultraviolet absorbing agent is contained: The content of the ultraviolet absorbing agent per unit area is 0.3 g / m 2 By setting the content of the ultraviolet ray blocking agent per unit area to 1.3 g / m or more, the necessary ultraviolet ray blocking rate can be ensured. 2 Above this level, the rate of increase in UV blocking performance also decreases, and the risk of economic loss increases as the cost of the increase is no longer justified.

[0045] Any of various conventionally known organic ultraviolet absorbents having an absorption maximum between wavelengths of 340 nm and 400 nm can be appropriately used as the ultraviolet absorbent contained in the adhesive for forming the adhesive layer 12. This allows light rays over 400 nm to be effectively captured, so that deterioration (yellowing) of the substrate resin layer 11 due to ultraviolet absorption can be suppressed without reducing the power generation amount of the solar cell module 10.

[0046] Examples of ultraviolet absorbers that can meet the above requirements include triazine-based ultraviolet absorbers and benzotriazole-based ultraviolet absorbers. Specific examples of triazine-based ultraviolet absorbers include 2,4,6-tris[2-hydroxy-4-[1-(isooctyloxycarbonyl)ethoxy]phenyl]-1,3,5-triazine, 2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3-5-triazine, and 2-(2-hydroxy-4-[1-(isooctyloxycarbonyl)ethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine. A preferred example of a commercially available triazine-based ultraviolet absorber is "TINUVIN405 (manufactured by BASF)". Similarly, examples of benzotriazole-based ultraviolet absorbers include "Adeka STAB LA-29 (manufactured by Adeka)". The above ultraviolet absorbents may be used in combination of two or more kinds, if necessary.

[0047] [Easy adhesive layer] The easy-adhesion layer 14 is a so-called primer layer, and is a layer having a function of improving the adhesion of the transparent protective sheet 1 to the back-side sealing material 2 made of an olefin-based resin or the like in the solar cell module 10. As shown in Fig. 2, it is formed on the other surface of the substrate resin layer 11 of the transparent protective sheet 1, which is opposite to the surface on which the weather-resistant resin layer 13 is laminated. This easy-adhesion layer 14 is also required to have the same transparency as the substrate resin layer 11 in order to maintain the transparency of the transparent protective sheet 1.

[0048] As the primer composition used to form the easy-adhesion layer 14, any of various conventionally known primer coating liquids that can satisfy the above-mentioned requirements regarding transparency can be used. For example, any of a primer composition containing an olefin resin and having an aqueous medium as the main solvent, and a primer composition containing a crosslinkable main resin and a crosslinking agent, etc., and having an organic medium as the main solvent can be selected.

[0049] <Method of manufacturing transparent protective sheet> The transparent protective sheet 1 can be produced by first producing a laminate in which a resin sheet constituting the weather-resistant resin layer 13 is bonded to the surface of a resin sheet constituting the base resin layer 11, and then forming an easy-adhesion layer 14 on the surface of this laminate opposite the weather-resistant resin layer.

[0050] [Joining of Base Resin Layer and Weather-Resistant Resin Layer] The resin sheets constituting the substrate resin layer 11 and the weather-resistant resin layer 13 are bonded by a dry lamination method via the adhesive layer 12 to obtain a laminate in which the substrate resin layer 11 and the weather-resistant resin layer 13 are integrated. Bonding by dry lamination via the adhesive layer 12 can be performed by applying the above-mentioned adhesive containing an ultraviolet absorber to an appropriate film thickness on one surface of the resin sheet constituting the substrate resin layer 11, and laminating the resin sheet constituting the weather-resistant resin layer 13 on the surface of the applied adhesive.

[0051] [Formation of easy-adhesion layer] A primer coating liquid such as the aqueous primer coating liquid is applied to the surface of the laminate obtained by the above process, in which the base resin layer 11 and the weather-resistant resin layer 13 are integrated, opposite to the surface on which the weather-resistant resin layer 13 is exposed, to form a coating film, thereby forming an easy-adhesion layer 14. Examples of the coating film formation method include gravure roll coating, reverse roll coating, wire bar coating, lip coating, air knife coating, curtain flow coating, spray coating, dip coating, screen printing, and brush coating. EXAMPLES

[0052] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples in any way.

[0053] <Manufacturing of transparent protective sheets> The transparent protective sheets of the Examples, Comparative Examples, and Reference Examples were produced using the following resin films, additive materials, adhesives, etc. The layer structure of each transparent protective sheet was the structure shown in Fig. 2, that is, a weather-resistant resin layer was bonded to one surface of a base resin layer via an adhesive layer, and an easy-adhesion layer was formed on the other surface.

[0054] (Base resin layer) As the resin film constituting the base resin layer of each transparent protective sheet, PET films formed to different thicknesses as shown in Table 1 were used.

[0055] (Weather-resistant resin layer) As the resin film constituting the weather-resistant resin layer of each transparent protective sheet, ETFE films formed to different thicknesses as shown in Table 1 were used.

[0056] (adhesive layer) The adhesive forming the adhesive layer of the transparent protective sheet of each Example and Comparative Example was manufactured by the following steps (a) to (c). The manufactured adhesive was dissolved in ethyl acetate as a solvent and gravure coated onto the surface of the resin sheet constituting the base resin layer. The coating amount was set so that the film thickness after curing was 5 μm for each transparent protective sheet. (a) Manufacturing of base material In a nitrogen atmosphere, 100 parts by mass of an aliphatic polycarbonate diol having a number average molecular weight of 1000 (manufactured by Asahi Kasei Chemicals Corporation, product name "Duranol T5651"), 1,6-hexanediol (5 parts by mass), isophorone diisocyanate (27.5 parts by mass), and ethyl acetate (132.5 parts by mass) were added to a flask equipped with a stirrer. -1 The mixture was heated under reflux until the absorption of isocyanate disappeared, to obtain a 50% solution of polyurethane diol. As the aliphatic polycarbonate diol, which is the main component, an aliphatic polycarbonate diol (manufactured by Asahi Kasei Chemicals Corporation, product name "DURANOL T5651") was prepared. The main component was prepared by using the polyurethane diol and aliphatic polycarbonate diol produced above, which are the main component components. This preparation was carried out by blending 15 parts by mass of the aliphatic polycarbonate diol with 100 parts by mass of the polyurethane diol. (b) Addition of UV absorbers A triazine-based ultraviolet absorber "TINUVIN 405 (product name, manufactured by BASF)" (molecular weight 583.76) was added to the base agent of the adhesive so that the content in the base agent of the adhesive, converted into solid content, was the content shown in Table 1. (c) Manufacturing of hardeners The curing agent used was a nurate of isophorone diisocyanate and a bifunctional polyurethane diisocyanate of hexamethylene diisocyanate (Duranate D101, manufactured by Asahi Kasei Chemicals Corporation). The mixing ratio (mass) of the nurate of isophorone diisocyanate: bifunctional polyurethane diisocyanate of hexamethylene diisocyanate was 40:60. The above mixing ratio (mass) is the solid mass ratio not including the solvent, but was adjusted to 50% solids during production. (d) Mixture of base resin and hardener The adhesive was manufactured using the base agent and hardener manufactured above. The base agent and hardener were mixed by dissolving them in a solvent to make 50% by mass (ethyl acetate solution). The hardener was added with 3-glycidoxypropyltrimethoxysilane as a silane coupling agent at a ratio of 1.2% to the total adhesive.

[0057] (Easy adhesion layer) A step of forming an easy-adhesion layer was carried out on the surface of the substrate resin layer to which the weather-resistant resin layer was bonded (the surface opposite to the weather-resistant resin layer). The following aqueous primer coating liquid was applied by gravure coating, and the applied coating liquid was dried at a drying temperature of 110°C for 2 minutes, and then cured at 40°C for 5 days to promote the curing of the adhesive layer and the formation of the easy-adhesion layer, thereby obtaining transparent protective sheets of each Example, Comparative Example, and Reference Example. The coating amount of each coating liquid was set so that the film thickness of the easy-adhesion layer after the above curing was 1 μm in each transparent protective sheet.

[0058] As the material for the aqueous primer coating liquid, an aqueous dispersion obtained by stirring and mixing the adhesive layer composition and the solvent made of the following materials was used. Acid-modified polyolefin resin As the base resin, a commercially available acid-modified polyolefin resin powder material ("Bondine (registered trademark)") manufactured by Tokyo Materials Co., Ltd. was used in each of the examples and comparative examples. Paraffin wax "Paraffin wax aqueous dispersion (EMUSTAR-0135, manufactured by Nippon Seiro Co., Ltd.)" was blended in the resin component of the easy-adhesion layer composition so that the content thereof, in terms of solid content, in the resin component was the content shown in Table 1. Other resins : "Epocross WS700, manufactured by Nippon Shokubai Co., Ltd." Added at a ratio of 5 parts by mass to 100 parts by mass of base resin. solvent A mixture of distilled water (76 parts by mass), isopropanol (23 parts by mass), and triethylamine (1 part by mass) was used as a solvent.

[0059] <Evaluation of transparent protective sheets> [Evaluation Example 1: Water vapor permeability, acetic acid permeability, acetic acid / water permeability ratio] In order to verify the effect of the present invention of promoting the release of acetic acid gas while maintaining high water vapor barrier properties, the water vapor permeability (pw) and acetic acid permeability (pa) of each transparent protective sheet were measured, and the acetic acid / water permeability ratio (pa / pw) was calculated. The results are shown in Table 1. The measurement method and the evaluation criteria for the measurement results were as follows. (Measurement method) The water vapor permeability (pw) was measured at a test temperature of 40°C according to JIS K 7126-1. The measurement device used was an oxygen permeability measuring device "OX-TRAN (manufactured by MOCON)." The acetic acid permeability (pa) was measured according to JIS K 7126-1 (GC method, T cell). The measurement temperature was 40°C. (Evaluation Criteria) Transparent protective sheets with a total thickness in the range of 150 μm to 165 μm were defined as the "thin film type," and transparent protective sheets with a total thickness in the range of 300 μm to 310 μm were defined as the "thick film type," with evaluation criteria for each type specified as shown in Table 1 below. (thin film type) Water vapor permeability (pw) (cm 3 / (m 2 24h atm) ○:1.2cm 3 / (m 2 ·24h · atm) or less ×:1.2cm 3 / (m 2 ·24h·atm) Acetic acid permeability (pa) (cm 3 / (m 2 24h atm) ○:1.5cm 3 / (m 2 ·24h · atm) or more ×:1.5cm 3 / (m 2 ·24h·atm) Acetic acid / water permeability ratio (pa / pw) ○: 1.4 or higher ×: Less than 1.4 (Thick film type) Water vapor permeability (pw) (cm 3 / (m 2 24h atm) ○:0.8cm 3 / (m 2 ·24h · atm) or less ×:0.8cm 3 / (m 2 ·24h·atm) Acetic acid permeability (pa) (cm 3 / (m 2 24h atm) ○:1.1cm 3 / (m 2 ·24h · atm) or more ×:1.1cm 3 / (m 2 ·24h·atm) Acetic acid / water permeability ratio (pa / pw) ○: 1.4 or higher ×: Less than 1.4

[0060] [Evaluation example 2: (Power generation efficiency maintenance rate of solar cell module)] In order to verify the effect of the present invention that the decrease in power generation efficiency of a solar cell module due to the influence of acetic acid gas can be effectively prevented, the output retention rate of the solar cell module was measured and calculated for solar cell module evaluation samples incorporating each transparent protective sheet. The results are shown in Table 1 as "output retention rate." The measurement method and evaluation criteria for the measurement results were as follows: (Creating samples for evaluating solar cell modules) Using each of the above transparent protective sheets as the protective sheet on the non-light-receiving side, and the following components as the transparent front substrate, solar cell element, and encapsulant sheet, "solar cell module evaluation samples" for the Examples and Comparative Examples were prepared. The samples were prepared by laminating the above components in the order of transparent front substrate / encapsulant sheet / solar cell element / encapsulant sheet / transparent protective sheet, and performing a vacuum heat lamination process under the lamination conditions below. (Transparent front board) White semi-tempered glass (AGC Fabritec Co., Ltd.: 3KWE33) (Solar cell element) A thin-film silicon solar cell element unit in which a thin-film silicon solar cell element device with a thickness of approximately 3 μm, consisting of an n-type transparent conductive film window layer, an n-type high-resistance buffer layer, a p-type CIS-based light absorption layer, and a metal back electrode layer, is mounted on a flexible substrate made of a resin film, was used as the above-mentioned solar cell element. (Sealing material sheet) As the encapsulant sheets constituting the test samples of the examples and comparative examples, the following encapsulant sheets were used. A resin sheet made by compounding 100 parts by mass of EVA (vinyl acetate content 28%, product name "EVAFLEX / EV250 grade", manufactured by Mitsui DuPont Polychemicals) with 1.5 parts by mass of crosslinking agent (product name "Lupersol101"), 0.5 parts by mass of crosslinking coagent (TAIC), 0.2 parts by mass of antioxidant (product name "NAUGARD-P"), 0.1 parts by mass of UV absorber (product name "Tinuvin7709"), and 0.3 parts by mass of UV absorber (product name "Cyasorb UV-531") using the T-die method at a film formation temperature of 90°C to a thickness of 400 μm. (Lamination conditions) Lamination was performed under standard curing conditions of bonding with a vacuum laminator at a pressure of 100 kPa at 150° C. for 15 minutes, and then leaving in a high temperature layer at 150° C. for 30 minutes. (Test Method) For each solar cell module evaluation sample, the Pmax value was measured before and after the dump heat test, the power generation efficiency maintenance rate was calculated, and the long-term power generation efficiency maintenance rate was evaluated based on the following evaluation criteria. The Pmax value is the maximum output value at the operating point where the output of the solar cell is maximum. Based on JIS-C8935-1995, the Pmax value of each evaluation sample was measured before and after the dump heat test. The dump heat test was performed by placing each of the above evaluation samples in an oven set to a temperature of 85°C and a humidity of 85%RH, and the power generation efficiency was measured before and after 3500 hours had passed, and the ratio was calculated. The cycle conditions of the oven were a cycle of going back and forth between temperatures of -20°C and 90°C, the time it took to change the temperature in the first stage was 5 hours, and the time to maintain the temperature was 1 hour, and the process of starting from -20°C, passing through 90°C, and returning to -20°C was considered as one cycle. The results are shown in Table 1 as "power generation efficiency maintenance rate." (Evaluation Criteria) ○: The power generation efficiency is maintained at 95% or more. △: The power generation efficiency maintenance rate is 90% or more and less than 95%. ×: The power generation efficiency maintenance rate is less than 90%.

[0061] [Evaluation example 3: (Light resistance)] A test for evaluating the light resistance (ultraviolet light resistance) of the transparent protective sheet of the present invention was carried out as follows. (Test Method) Each transparent protective sheet was placed in a Super UV tester (Iwasaki Electric EYESUPER UV TESTER SUV-W151) at 1000W / m 2 After that, the condition of the surface of each sheet was visually observed. (Evaluation Criteria) ◯: No visible yellowing of the film occurred. ×: Yellowing of the film was visible to the naked eye.

[0062] [Test Example 4: (Economics)] The transparent protective sheets 1 of each of the Examples, Comparative Examples, and Reference Examples were evaluated for economic efficiency mainly from the viewpoint of material cost. The transparent protective sheets of Reference Examples 1 and 2, in which the entire layer is made of ETFA instead of PET, were evaluated as being unfavorable in terms of economic efficiency because it is clear that this will lead to a rise in material costs. It should be noted that although it has been confirmed that these have inferior water vapor permeability compared to the Examples, it is clear that this is difficult to implement from an economic standpoint, so evaluations were not made on the acetic acid / water permeability ratio, power generation efficiency maintenance rate, and light resistance.

[0063] [Table 1]

[0064] From Table 1, it can be confirmed that the transparent protective sheet of the present invention is a transparent protective sheet that uses economical polyethylene terephthalate as a base resin, and that maintains high water vapor barrier properties that prevent the intrusion of water vapor from outside the solar cell module, while at the same time promoting the release of harmful gases (acetic acid gas) generated inside the module to the outside of the module. [Explanation of symbols]

[0065] 1 Transparent protective sheet 11 Base resin layer 12 Adhesive layer 13 Weather-resistant resin layer 14 Easy adhesive layer 2 Back side sealing material 3. Surface sealing material 4 Transparent front board 5. Solar cell element 10. Solar Cell Module

Claims

1. A transparent resin sheet having a light transmittance of 70% or more at a wavelength of 400 nm or more and 1200 nm or less, The transparent resin sheet is a multi-layered resin sheet in which a base resin layer occupying 75% or more of the total thickness in terms of thickness ratio and a weather-resistant resin layer are laminated, and the multi-layered resin sheet is configured without including either a vapor deposition layer made of an inorganic compound or a thin film layer made of an inorganic compound, and the total thickness of the entire multi-layered resin sheet exceeds 300 μm, The base resin layer is polyethylene terephthalate, The weather-resistant resin layer is a copolymer of tetrafluoroethylene and ethylene, The water vapor permeability (pw) of the entire multi-layered resin sheet of the transparent resin sheet, measured at a test temperature of 40° C. according to JIS K 7126-1, is 0.8 cm 3 / (m 2 ・24h・atm) or less, The ratio (pa / pw) of the acetic acid permeability (pa) measured at a test temperature of 40° C. according to JIS K 7126-1 to the water vapor permeability (pw) of the entire multilayer resin sheet is 1.4 or more. A transparent protective sheet for solar cell modules.

2. The total thickness of the multilayer resin sheet as a whole is 310 μm or less. The transparent protective sheet for a solar cell module according to claim 1 .

3. The thickness of the base resin layer is more than 90% of the total thickness of the entire multilayer resin sheet. The transparent protective sheet for a solar cell module according to claim 1 or 2.

4. A solar cell element; a front surface side sealing material and a back surface side sealing material laminated on both surfaces of the solar cell element; A solar cell module comprising: a protective sheet laminated on a surface of either the front surface-side sealing material or the back surface-side sealing material, the solar cell element is a bifacial solar cell element, the front surface-side sealing material and the back surface-side sealing material each have an ethylene-vinyl acetate copolymer (EVA) as a base resin, and the light transmittance is 70% or more; The protective sheet is the transparent protective sheet according to claim 1 or 2, which is disposed on the outermost surface of the solar cell module. Solar cell module.

Citation Information

Patent Citations

  • Solar module back veneer comprising non-solvent bonding layers and manufacturing method thereof

    CN102569451A

  • Photovoltaic device

    JP2005276939A

  • Backsheet for solar cell modules and method for repairing the same

    JP2010519742A

  • Polymer sheet and method for producing the same, back sheet for solar cell using the polymer sheet, solar cell module, and polymer water dispersion

    JP2011167938A

  • Sealing film integrating rear side protection member for solar cell and production method therefor, solar cell using it and manufacturing method therefor

    JP2012151399A